Al-Hasakfi’s Notes on Nasafi explanation of Al-Manar - Ahmed , Yassin (Islamic Sciences Journal, 2023)
ABSTRACT Scientists from the nation took the lead of scientific interface, and they were the axis for those who came after them, and among those scholars (the Imam Al-Nasafi) whose book (Al-Manar) is the axis of explanation, comment, commentary, abbreviation and systems .. from the eighth century AH to the present day, where he wrote more than fifty books, and many of the scientific theses that discussed his views and his way of presenting the origins of the Hanaf. Among the explanations of the book Al-Manar is (elaborating the lights) by Hasakfi, and this explanation received a great attention; and it was taken as a curriculum in some legal colleges. Imam al-Hasakfi had comments on his explanation of Al-Manar, which it was, explained, and commented on. It was intended that scholars throughout history have been reviewing their statements, scrutinizing their consideration, and correcting each other, with a scientific method fraught with the highest methods of research etiquette and debate; Let us approach their follow, and imitate them in criticizing sayings in our contemporary time.